2013
DOI: 10.1063/1.4816746
|View full text |Cite
|
Sign up to set email alerts
|

Vapor transport deposition and epitaxy of orthorhombic SnS on glass and NaCl substrates

Abstract: Polycrystalline SnS, Sn2S3, and SnS2 were deposited onto glass substrates by vapor transport deposition, with the stoichiometry controlled by deposition temperature. In addition, epitaxial growth of orthorhombic SnS(010) films on NaCl(100) with thicknesses up to 600 nm was demonstrated. The in-plane [100] directions of SnS and NaCl are oriented approximately 45° apart, and the translational relationship between SnS and NaCl was predicted by density functional theory. The epitaxial SnS is p-type with carrier co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 25 publications
6
43
1
Order By: Relevance
“…6,41 The calculated formation enthalpies for defects associated with the presence of Na and Mo atoms are shown in Fig. 6.…”
Section: E Substrate-related Defects: Na and Momentioning
confidence: 99%
“…6,41 The calculated formation enthalpies for defects associated with the presence of Na and Mo atoms are shown in Fig. 6.…”
Section: E Substrate-related Defects: Na and Momentioning
confidence: 99%
“…21 The fact that Sn chalcogenides can exist in three different bulk crystal structures with different chalcogen contents (e.g., SnS 2 , Sn 2 S 3 , and SnS) not only makes these materials interesting but also causes complications: The absence of a fixed stoichiometry implies that several phases may be present both in source materials (precursor powders, evaporation materials, and sputtering targets) and in the resulting films. 8,22 Sousa et al recently suggested thermal annealing of sputtered SnS 2 films as a possible route toward single-phase SnS for photovoltaics, 23 using the fact that the composition can be continuously varied across the entire spectrum of materials via introduction of defects such as sulfur vacancies (V S ). Such defects, which are likely to be abundant as they can be produced in material synthesis as well as during thermal processing or by interaction with energetic electron or ion beams, can strongly affect light absorption and emission.…”
mentioning
confidence: 99%
“…The stac form CZTS with a bandgap of 1.4 device was produced using Mo/CZTS/CdS/ZnO/Al:ZnO and and rectifying behavior (see Fig. 2 SnS solar cell devices were produced by vapor transport deposition (VTD) [9], which is a proven low-cost manufacturing method for commercial CdTe-based solar modules [11,12]. If high performance SnS-based solar cells can be fabricated using VTD, commercial adoption can also leverage existing manufacturing equipment.…”
Section: Figure 2: Sem Cross Section Of C Reproduced From [8] With Rementioning
confidence: 99%